Direct analysis in real time—Mass spectrometry (DART‐MS) in forensic and security applications. Issue 2 (6th June 2016) - Pavlovich, Matthew J.; Musselman, Brian; Hall, Adam B.
Abstract : Over the last decade, direct analysis in real time (DART) has emerged as a viable method for fast, easy, and reliable "ambient ionization" for forensic analysis. The ability of DART to generate ions from chemicals that might be present at the scene of a criminal activity, whether they are in the gas, liquid, or solid phase, with limited sample preparation has made the technology a useful analytical tool in numerous forensic applications. This review paper summarizes many of those applications, ranging from the analysis of trace evidence to security applications, with a focus on providing the forensic scientist with a resource for developing their own applications. The most common uses for DART in forensics are in studying seized drugs, drugs of abuse and their metabolites, bulk and detonated explosives, toxic chemicals, chemical warfare agents, inks and dyes, and commercial plant and animal products that have been adulterated for economic gain. This review is meant to complement recent reviews that have described the fundamentals of the ionization mechanism and the general use of DART. We describe a wide range of forensic applications beyond the field of analyzing drugs of abuse, which dominates the literature, including common experimental and data analysis methods. © 2016 Wiley Periodicals, Inc. Mass Spec Rev 37:171–187, 2018.